BCR-ABL1-positive acute lymphoblastic leukemia following successful treatment of acute promyelocytic leukemia: case report - Fu, Shuang; Li, Mengqi; Wang, Hongtao (Frontiers in Pharmacology, 2023)
Acute promyelocytic leukemia (APL) is currently considered a disease with a higher cure rate. And cases of secondary malignant tumors following successful APL treatment are rare. Here we described a rare case of a 29-year-old man who was treated for APL in 2019 and developed BCR-ABL1-positive acute lymphoblastic leukemia two years later. The patient responded well to tyrosine kinase inhibitors and chemotherapy, and achieved a molecular remission. Although APL usually has a good prognosis, the prognosis of its secondary malignancies is uncertain. There are no effective measures to prevent the occurrence of secondary tumors. Continuing to increase the monitoring frequency of laboratory tests, especially the molecular biomarkers, is essential for the diagnosis and treatment of secondary malignancies after the patients achieving complete remission.